Analysis of the Relationship of Professionals towards the Vertical Equity of the Slovenian Tax System and Its Comparison with Croatia, Bosnia and Herzegovina and the USA - Jelena Klopčič; Maja Klun (Central European Public Administration Review)
Vertical equity states that taxpayers whose positions are not the same should be treated differently while taking into consideration all the relevant characteristics. The main purpose of using the vertical equity principle is to require the redistribution of income in a way that reduces the income inequality of the society. The presented research aims to check the opinion of Slovenian tax system professionals on the principle of vertical equity. Slovenian results have been compared to a similar analysis carried out in Croatia, and partly with survey results from Bosnia and Herzegovina and the United States of America. The results show that the professional public agrees with the principle of vertical equity in the implementation of tax systems. All of the compared countries are similarly favourable towards vertical equity. However, this is also affected by the current tax arrangements of the individual countries.